A study on the uniaxial behavior of hybrid graded fiber reinforced concrete with glass and steel fibers. (2020) - Prathipati, S.R.R. Teja; Rao, C.B.K.
Abstract: Blending of fibers with different types and different geometries into the concrete was called Hybrid Graded Fiber Reinforced Concrete (HyGrFRC), which is a sub-classification of Hybrid Fiber Reinforced Concrete (HyFRC). The complete behavior of HyGrFRC was not wholly established to date, and there is a need to explore the synergy of HyGrFRC using different fiber types and fiber lengths. In this study, crimped steel fibers and Alkali Resistant (AR) glass fibers with a total fiber volume of 1.65% were used in different proportions, and the uniaxial compressive response of the HyGrFRC was computed. A comparison was made between HyFRC and HyGrFRC in terms of strength properties and uniaxial compressive behavior. In both HyFRC and HyGrFRC mixes, glass fibers improved the pre-peak behavior, and steel fibers improved the post-peak behavior of concrete, thereby exhibiting a positive synergy in combining glass and steel fiber into the concrete. It was observed that the strength, toughness index, and ductility values of the resulting HyGrFRC mixes were significantly higher when compared to HyFRC mixes, and that shows there exists a positive synergy in hybridizing graded fibers into the concrete.